Governmental basis for household waste sorting behavior : extending the theory of planned behavior - Muhammad Abduh,; Budianta, Dedik; Arinafril,; Lili Erina, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Early introduction of household waste sorting behavior (WSB) can demote common environmental pollution and and its effects. Source of waste in Indonesia is households which specifically come from food scraps, yard waste, wrapping materials, even hazardous and non-hazardous materials, recyclable and nonrecyclable waste, organic and non-organic. In Indonesia, household waste was sorted only 23,83%. This study investigated factors correlated with household waste sorting behavior in Indonesia by applying the theory of planned behavior (TPB). This is a cross-sectional research uses a unique dataset collected by the Indonesian government, including the Village Potential Statistics (VPS) Year 2011 and Environmental Care Behavior Survey (ECBS) Year 2013. Factors related to household WSB were determined by exercising a multivariable logistic regression model working manual backward stepwise regression. All of model, almost all factors of the planned behavior theory and its extension were significantly associated with household WSB except perceived behavioral control (precise enough: OR = 1.02, 95% CI: 0.88, 1.19), not build affect an educational environmental infrastructure (OR = 1.01, 95% CI: 0.99, 1.03) and not build affect a production skill (OR = 1.01, 95% CI: 0.98, 1.04). This study resulted intention, attitude, and subjective norm as a determinant of household waste sorting behavior after considering the share of several government-based variables. The existence of community empowerment programs such as environmental infrastructure improvement, economic capacity building and community social capacity initiative contribute and could be part of productive design to implement household waste sorting behavior.